Picturing (as) Resistance: Studying Resistance and Well-Being of Indigenous Girls and Young Women in Addressing Sexual Violence (LEARNing Landscapes, 2017)
The health and well-being of young people remains a critical issue. For Indigenous girls and young women in Canada and South Africa, the situation is exacerbated by high rates of sexual violence. The article draws on examples of artworks and close readings of several images of resistance produced by Indigenous girls and young women participating in a six-year study that seeks to address sexual violence in the two countries. Exploring resistance is an understudied area in relation to young people and well-being. Building on our visual research and fieldwork, we posit that the idea of “picturing (as) resistance” through the various participatory visual and arts-based tools is a promising area of investigation in relation to wellbeing.
Keywords: well-being; health; young girls; women; sexual violence; resistence; visual research; participatory; picturing